The use of human sewage screening for community surveillance of hepatitis E virus in the UK - Smith, Donald B. (J Med Virol, 2015)
Hepatitis E virus sequences were detected by RT‐PCR in 14/15 (93%) of untreated sewage samples from Edinburgh, Scotland, UK. Phylogenetic analysis of amplicons at limiting dilution revealed the co‐circulation of multiple variants of HEV‐3, with a pattern of diversity matching that observed in a local cohort of HEV‐infected hepatitis patients. J. Med. Virol. 88:915–918, 2016. © 2015 The Authors. Journal of Medical Virology Published by Wiley Periodicals, Inc.